2016
DOI: 10.1515/aucft-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of Essential Oils from Black Pepper, Cumin, Coriander and Cardamom Against Some Pathogenic Microorganisms

Abstract: Four popular spices black pepper (Piper nigrum L.), cumin (Cuminum cyminum L.), coriander (Coriandrum sativum L.) and cardamom (Elettaria cardamomum) were analyzed for their oil composition by GC-MS. Thirty compounds were identified in the black pepper oil and the main components were β-caryophyllene (20.225 %), sabinene (18.054 %), limonene (16.924 %), α-pinene (9.171 %) and α-phellandrene (5.968 %). Twenty five compounds were identified in the cumin oil – cuminaldehyde (30.834 %), 3-caren-10-al (17.223 %), β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
(14 reference statements)
2
12
2
Order By: Relevance
“…33 A similar study has also been carried by Teneva et al, the essential oil E. cardamomum showed effectiveness against E. coli, S. aureus, Salmonella sp., and P. vulgaris with a variable susceptibility. 34 More recently our study is also supported by Mutlu-Ingok et al, who observed that the E. cardamomum varieties with high content of α-terpinyl acetate and 1,8-cineole were more active against Campylobacter coli and Campylobacter jejuni . 35 In the present study, we were now reporting that, the role of α-terpinyl acetate and 1,8-cineole showed potentially more effective against microbes as compared to less content originating varieties of α-terpinyl acetate and 1,8-cineole.…”
Section: Discussionsupporting
confidence: 85%
“…33 A similar study has also been carried by Teneva et al, the essential oil E. cardamomum showed effectiveness against E. coli, S. aureus, Salmonella sp., and P. vulgaris with a variable susceptibility. 34 More recently our study is also supported by Mutlu-Ingok et al, who observed that the E. cardamomum varieties with high content of α-terpinyl acetate and 1,8-cineole were more active against Campylobacter coli and Campylobacter jejuni . 35 In the present study, we were now reporting that, the role of α-terpinyl acetate and 1,8-cineole showed potentially more effective against microbes as compared to less content originating varieties of α-terpinyl acetate and 1,8-cineole.…”
Section: Discussionsupporting
confidence: 85%
“…These figures are similar to a previous study involving Vietnamese black pepper essential oil where 3‐carene was reported to be one of the major constituents (29.21%) (Tran et al, ). However, presented results were different from compositional results of essential oils of black pepper harvested from other areas where caryophyllene (about 10%–20%) and limonene (about 10%) were the major compounds (Feng, Jiang, Wang, & Li, ; Han, Beaumont, Rodriguez, & Bahr, ; Kumoro, Hasan, & Singh, ; Morshed, ; Teneva et al, ).…”
Section: Resultscontrasting
confidence: 81%
“…Additionally, we have previously reported that the green cardamom essential oil was active against a large panel of Gram-positive bacteria (mean diameter= 21.77 mm), cariogenic bacteria (mean diameter= 19.51 mm) and fungi (mean diameter= 39.5 mm), with MICs values ranging from 0.023 to 0.046 mg/mL for all bacterial and fungal strains tested [ 25 ]. Recently, Teneva and coworkers [ 33 ] reported that the green cardamom oil (chemotype α-terpinyl acetate 39.03 %, eucalyptol 31.53 %) was active against pathogenic E. coli ATCC 25922, E. coli ATCC 8739, Salmonella sp., S. aureus ATCC 6538P, and P. vulgaris strains with a diameters of inhibition zones between 8 and 10 mm and MICs values from 60 to >600 ppm. In 2017, Mutlu-Ingok and Karbancioglu-Guler [ 34 ] reported that the green cardamom oil (chemotype α-terpinyl acetate 43.4%, eucalyptol 29.2%) was active against Campylobacter jejuni and Campylobacter coli with a diameter of growth inhibition zone ranging from 24.75 mm to 25.58, respectively.…”
Section: Discussionmentioning
confidence: 99%